Liu Kang Colourful Modernist - Yeo, Wei Wei (National Gallery Singapore, 2011)
Liu Kang, one of Singapore's first generation artists, was a seminal observer, commentator, and visionary of modernity in Singapore art history. The contexts in which his works were created consist of a colourful map of diverse cultures, places and influences, spanning China, Europe and Southeast Asia. In this monograph, the cross-cultural richness in Liu Kang's way of seeing and art making are explored in four essays by curators and art researchers. These essays present fresh insights into the artist's engagement with European and Chinese modernisms in a Singaporean context.